New Insights into the Roles of Yes-Associated Protein (YAP1) in Colorectal Cancer Development and Progression - Fariba Dehghanian (Shiraz University of Medical Sciences, 2019)
Yes-associated protein (YAP1), the downstream effector of the Hippo pathway, plays important roles in the regulation of tissue reconstruction,stem cell proliferation, and development of different cancers. The regulation of YAP1 phosphorylation, YAP1 expressionlevel, and its cellular localization have been considered in cancer development. There are different experimental evidences thatindicate that YAP1 activation results in tumorigenesis, tumor progression, and metastasis. YAP1 is a transcription co-activator, andits dysregulation has been suggested in various cancers including colorectal cancer (CRC). The localization of YAP1 in the nucleusresults in YAP1 interactions with different transcription factors to promote the expression of genes involved in cell proliferation,metastasis, and stem cell maintenance. However, a number of studies have been reported the tumor suppressor role of YAP1 in CRC.Therefore, a better understanding of the YAP1 regulation could be helpful for prevention, diagnosis, and treatment of CRC. In thisreview, we will discuss different roles of YAP1 in CRC progression through the regulatory roles of long non-coding RNAs (LncRNAs),microRNAs (miRNAs) and circular RNAs (CircRNAs) in YAP1 regulation.